Evaluation of the intercanine distance in newborns with cleft lip and palate using 3D digital casts - Bianca Zeponi Fernandes Mello; Viviane Mendes Fernandes; Cleide Felicio Carvalho Carrara; Maria Aparecida Andrade Moreira Machado; Daniela Gamba Garib; Thais Marchini Oliveira (University of São Paulo, 2013)
OBJECTIVE: The purpose of this present study was to compare, by means of 3D digital casts, the anterior transverse dimension of the dental arch of newborns with and without cleft lip and palate. MATERIAL AND METHODS: The sample was composed of ninety-four children aged from 3 to 9 months divided into three study groups: Group I - children without craniofacial deformities (control group); Group II - children with unilateral cleft lip and palate; Group III - children with bilateral cleft lip and palate. Impressions were executed before lip and palate repair in patients with clefts. Dental casts were digitized using a 3D scanner linked to a computer. Measurements of the intercanine distance were measured on the digital casts. Intergroup comparisons were performed using ANOVA (p<0.05). RESULTS: The results showed a mean of 36.5 mm for unilateral cleft lip and palate group, 34.8 mm for bilateral cleft lip and palate group and 27.52 mm for the control group. There was a statistically significant difference between the control group and both groups of patients with cleft lip and palate. There was no statistically significant difference between complete unilateral and bilateral cleft lip and palate groups. CONCLUSIONS: Patients with complete cleft lip and palate were born with an increased anterior dimension of the maxillary dental arch compared to non cleft patients.